2016
DOI: 10.1128/aem.00204-16
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Complete Genome Sequence of Algibacter alginolytica sp. nov., a Novel Seaweed-Degrading Bacteroidetes Bacterium with Diverse Putative Polysaccharide Utilization Loci

Abstract: eThe members of the phylum Bacteroidetes are recognized as some of the most important specialists for the degradation of polysaccharides. However, in contrast to research on Bacteroidetes in the human gut, research on polysaccharide degradation by marine Bacteroidetes is still rare. The genus Algibacter belongs to the Flavobacteriaceae family of the Bacteroidetes, and most species in this genus are isolated from or near the habitat of algae, indicating a preference for the complex polysaccharides of algae. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(44 citation statements)
references
References 96 publications
(98 reference statements)
1
43
0
Order By: Relevance
“…3A). Fucosidase activity, which is involved in the degradation of polysaccharides (Sun et al, 2016), was low at the beginning of the experiment but displayed a maximum on day 223, when the peak in esterase activity was observed ( Fig. 3F).…”
Section: Resultsmentioning
confidence: 99%
“…3A). Fucosidase activity, which is involved in the degradation of polysaccharides (Sun et al, 2016), was low at the beginning of the experiment but displayed a maximum on day 223, when the peak in esterase activity was observed ( Fig. 3F).…”
Section: Resultsmentioning
confidence: 99%
“…Glimmer 3.02 was used to predict coding DNA sequences (CDSs). A BLAST search was then conducted for CDSs in some widely used databases: NCBI non-redundant (NR) database, Swiss-Prot, COGs, Gene Ontology (GO) and KEGGs [48,49]. GO, an important bioinformatics tool, unified expressions of gene and genetic products in all species [50].…”
Section: Function Annotation Of B Velezensis Lc1mentioning
confidence: 99%
“…Further investigation found that three of the taxa showing the highest co-occurrence scores with the driving taxon T. dicentrarchi (Formosa sp. Hel1_33_131, Cellulophaga algicola and Algibacter alginolytica) are associated with algae (Becker, Scheffel, Polz, & Hehemann, 2017;Bowman, 2000;Sun et al, 2016).…”
Section: Diversity Analysesmentioning
confidence: 99%